2017
DOI: 10.3389/fpls.2017.00512
|View full text |Cite
|
Sign up to set email alerts
|

Plastic-Film Mulching for Enhanced Water-Use Efficiency and Economic Returns from Maize Fields in Semiarid China

Abstract: Film mulch has gradually been popularized to increase water availability to crops for improving and stabilizing agricultural production in the semiarid areas of Northwest China. To find more sustainable and economic film mulch methods for alleviating drought stress in semiarid region, it is necessary to test optimum planting methods in same cultivation conditions. A field experiment was conducted during 2013 and 2014 to evaluate the effects of different plastic film mulch methods on soil water, soil temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…In the current study, plant height, shoot and root biomass, SPAD readings, and ear weight and number were greater for all black plastic BDM and PE mulch treatments compared with bare ground, WeedGuardPlus, and Clear Organix AG treatments. Other studies have also reported increased sweet corn plant vigor and yield with the use of PE mulches compared with bare ground (Rajablariani and Sheykhmohamady, 2015;Xu et al, 2015;Zandstra et al, 2007;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In the current study, plant height, shoot and root biomass, SPAD readings, and ear weight and number were greater for all black plastic BDM and PE mulch treatments compared with bare ground, WeedGuardPlus, and Clear Organix AG treatments. Other studies have also reported increased sweet corn plant vigor and yield with the use of PE mulches compared with bare ground (Rajablariani and Sheykhmohamady, 2015;Xu et al, 2015;Zandstra et al, 2007;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…These benefits can lead to earlier harvest and increased crop yield (Liu et al, 2009;Steinmetz et al, 2016). Zhang et al (2017) evaluated the effects of PE mulch (8 mm, Gansu Tianbao Plastic Plant, China) on soil temperature, soil moisture, water use efficiency (WUE; yield per unit water), yield, and revenue of grain corn. Soil temperatures (5 to 25 cm deep) and soil moisture (0 to 200 cm deep) were greater in field plots with PE mulch than in bare ground, leading to increased WUE and yield in the PE mulch treatment.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The climate conditions during the maize cropping season were more favourable in the first year, with higher temperatures and more hours of sunshine than in the second year (Figure 1). However, the effect of FM on increasing maize yields was much better in the second year than in the first year because FM warmed the soil and prevented water loss under more severe soil conditions with low temperatures and less precipitation (Yi, Shenjiao, Shiqing, Xinping, & Fang, 2010;Zhang et al, 2017). Net primary production (NPP) provided the primary input of C to the soil and was sensitive to climate conditions.…”
Section: Crop Productivity and Net Primary Production (Npp)mentioning
confidence: 99%